1) х²-12х+16=0; 2) x²-28x+16=0; 3) x²-14x+44=0
Пошаговое объяснение:
По теореме Виета для приведенного квадратного уравнения:
{х1+х2= -b= 6
{x1x2= c= 4
1) х'1=2х1, х'2=2х2
{х'1+х'2= 2х1+2х2= 2(х1+х2)
{х'1х'2= 2х1×2х2= 4х1х2
{2(х1+х2)= 6×2= 12= -b'
{4x1x2= 4×4= 16= c'
х²-12х+16=0
2) х'1=х1², х'2=х2²
{х'1+х'2= х1²+х2² = (х1)²+2х1х2+(х2)²-2х1х2= (х1+х2)²-2х1х2
{х'1х'2= х1²х2²= (х1х2)²
{(х1+х2)²-2х1х2= 6²-2×4= 28= -b'
{(x1x2)²= 4²= 16= c'
x²-28x+16=0
3) x'1=x1+4, x'2=x2+4
{x'1+x'2= x1+4+x2+4= x1+x2+8
{x'1x'2=(x1+4)(x2+4)= x1x2+4x1+4x2+16= x1x2+4(x1+x2)+16
{x1+x2+8= 6+8= 14 = -b'
{x1x2+4(x1+x2)+16= 4+4×6+16= 44= c'
x²-14x+44=0
1) х²-12х+16=0; 2) x²-28x+16=0; 3) x²-14x+44=0
Пошаговое объяснение:
По теореме Виета для приведенного квадратного уравнения:
{х1+х2= -b= 6
{x1x2= c= 4
1) х'1=2х1, х'2=2х2
{х'1+х'2= 2х1+2х2= 2(х1+х2)
{х'1х'2= 2х1×2х2= 4х1х2
{2(х1+х2)= 6×2= 12= -b'
{4x1x2= 4×4= 16= c'
х²-12х+16=0
2) х'1=х1², х'2=х2²
{х'1+х'2= х1²+х2² = (х1)²+2х1х2+(х2)²-2х1х2= (х1+х2)²-2х1х2
{х'1х'2= х1²х2²= (х1х2)²
{(х1+х2)²-2х1х2= 6²-2×4= 28= -b'
{(x1x2)²= 4²= 16= c'
x²-28x+16=0
3) x'1=x1+4, x'2=x2+4
{x'1+x'2= x1+4+x2+4= x1+x2+8
{x'1x'2=(x1+4)(x2+4)= x1x2+4x1+4x2+16= x1x2+4(x1+x2)+16
{x1+x2+8= 6+8= 14 = -b'
{x1x2+4(x1+x2)+16= 4+4×6+16= 44= c'
x²-14x+44=0
3=4x+8
4x=3-8
4x=-5
x=-5:4
x=-1,25
-7=5(x+5)
-7=5x+25
5x=-7-25
5x=-32
x=-32:5
x=-6,4
9(x+7)=-x
9x+63=-x
9x+x=-63
10x=-63
x=-63:10
x=-6,3
5(x-3)=4x
5x-15=4x
5x-4x=15
x=15
4(x+6)=x
4x+24=x
4x-x=-24
3x=-24
x=-24:3
x=-8